Bibliomatric Analysis in Natural Tourism 2023 - Yanti, Wikey Damai; Rahmadanti, Ravanie Hanifa; Pradini, Gagih; Kusumaningrum, Anisa Putri; Ardani, Putri Aulia (Peneliti.net, 2023)
This research discusses the use of bibliometric analysis in various research fields. This journal provides examples of studies conducted in the fields of sustainable tourism, climate change, halal tourism, cultural tourism, and digital marketing. This journal also explains the use of Google Scholar as a research data provider and VOS Viewer as a research tool for bibliometric analysis. The methods used in this research include determining keywords, conducting an initial search, refining search results, compiling statistical data, and analyzing data. The results and discussion sections present the research findings, including publication and citation analysis, visualization, author ownership, and network analysis. The table presents a data matrix comparison of the initial search results and the revised search results.